Original Article Accuracy between Functional Swallowing and Knebelman Craniometric Method to Measure Occlusal Vertical Dimension in Total Denture Wearers: A Quasi-experimental Study - Huamani-Echaccaya 2, Jose Luis (2021)
Objective: The objective was to determine the accuracy between functional swallowing (FS) and the Knebelman craniometric method (KCM) to measure occlusal vertical dimension (OVD) in total denture wearers. Materials and Methods: A quasi-experimental, prospective study was conducted considering the KCM diagnostic method as the gold standard compared to FS. All the totally edentulous patients attended at the School of Dentistry of the Universidad Nacional Mayor de San Marcos (n = 32) in 2018–2019 were evaluated. Previous informed consent was obtained from all patients. A Knebelman’s Craniometer was used to obtain longitudinal measurements measured in millimeters. The measurement was made with the Knebelman Craniometer by placing the tip into the external auditory canal inside the right meatus. On the other hand, for the FS method, the patients were seated comfortably with their back supported and their head in a natural position. Both upper and lower rollers were inserted into the mouth and the patient was instructed to swallow saliva for a period of 5min. Results: When comparing the measurement of the OVD of KCM versus FS according to sex, men presented an OVD of 68.1 ± 3.9mm, being 64.1 ± 3.8mm in women. Accuracy was evaluated with an analysis of concordance between FS and the KCM in the determination of OVD in totally edentulous patients with a value of 0.97 (confidence interval = 0.31–0.99) (P = 0.013). Conclusions: There is a good concordance between the FS method and the KCM at the time of determining the OVD of edentulous patients using total prostheses